TNFα, PDGF, and TGFβ synergistically induce synovial lining hyperplasia via inducible PI3Kδ. Issue 1 (January 2015) - Shibuya, Hideyuki; Yoshitomi, Hiroyuki; Murata, Koichi; Kobayashi, Shio; Furu, Moritoshi; Ishikawa, Masahiro; Fujii, Takayuki; Ito, Hiromu; Matsuda, Shuichi
Abstract Objectives. To determine the mechanism underlying hypertrophic synovium in rheumatoid arthritis (RA). Methods. We examined micromass cultures of fibroblast-like synoviocytes (FLSs) stimulated with tumor necrosis factor α (TNFα), platelet-derived growth factor (PDGF), and/or transforming growth factor β (TGFβ). The hypertrophic architecture of the micromasses, expression of phosphoinositide 3 kinase (PI3K) isoforms, and persistent activation of PI3K-Akt pathways were investigated. FLSs transfected with siRNA were also examined in the micromass cultures. Results. The combination of TNFα, PDGF, and TGFβ (TPT condition) induced obvious hypertrophic architecture of the intimal lining layer in FLSs in micromass cultures, and was accompanied by upregulated expression of matrix metalloproteinase-3 (MMP3), Cadherin-11, and PI3Kδ. In monolayer FLSs, the TPT condition enhanced the expression of PI3Kδ and persistent activation of the PI3K-Akt pathway. Knockdown of PI3Kδ significantly inhibited the formation of the hypertrophic synovial lining in the TPT condition. Conclusions. These results collectively indicate that inducible PI3Kδ plays a crucial role in persistent activation of PI3K-Akt in FLSs, and in the formation of a hypertrophic synovial lining. PI3Kδ may be an alternative treatment target for the regulation of proliferative synovium in RA.